ANALISIS PERGESERAN AKTIVITAS PERORI PETANI LOKAL DAYAK KENINJAL DI DUSUN RIBANG RABING KABUPATEN MELAWI - Julianti, Susi; Sulistyarini, Sulistyarini; Fatmawati, Fatmawati (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Abstract This study aims to find out the shift in the activities of perori local farmers Dayak Keninjal in Ribang Rabing hamlet. The research method used is descriptive in the form of qualitative research. The data sources of this research are the village head of Bina Jaya, the hamlet head of Ribang Rabing, the traditional figure of Ribang Rabing hamlet and local farmers Dayak Keninjal hamlet Ribang Rabing. The data obtained are sourced from the bina jaya village document, the results of observations directly to the field and interview with informants. The results showed that perori activities of the local farmers Dayak Keninjal in the hamlet of Ribang Rabing had undergone a shift and were rarely carried out again, this is evidenced by changes in the system of perori activity so that the wage system emerged. The forms of planned change is the change in the system of perori activities, changes in livelihoods, shifts in agricultural equipment, and changes to agricultural pattern traditions. While the form of unplanned change is a change in the values of perori and changes in attitudes and behavior patterns among groups in society. Keywords: Dayak Keninjal, Shift in Perori Activity